Proceedings of the 57th Annual Meeting of the Association for Computational Linguistics 2019
DOI: 10.18653/v1/p19-1228
|View full text |Cite
|
Sign up to set email alerts
|

Compound Probabilistic Context-Free Grammars for Grammar Induction

Abstract: We study a formalization of the grammar induction problem that models sentences as being generated by a compound probabilistic context-free grammar.In contrast to traditional formulations which learn a single stochastic grammar, our context-free rule probabilities are modulated by a per-sentence continuous latent variable, which induces marginal dependencies beyond the traditional context-free assumptions. Inference in this grammar is performed by collapsed variational inference, in which an amortized variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
235
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(239 citation statements)
references
References 66 publications
4
235
0
Order By: Relevance
“…Other linguistic constraints and heuristics such as constraints of root nodes (Noji, Miyao, and Johnson 2016), attachment rules (Naseem et al 2010), acoustic cues (Pate and Goldwater 2013), and punctuation as phrasal boundaries (Seginer 2007a;Ponvert, Baldridge, and Erk 2011) have also been used in induction. More recently, neural PCFG induction systems (Jin et al 2019;Kim et al 2019;Kim, Dyer, and Rush 2019) and unsupervised parsing models (Shen et al 2018(Shen et al , 2019Drozdov et al 2019) have been shown to predict accurate syntactic structures. These more complex neural network models may not contain explicit biases, but may contain implicit confounding factors implemented during development on English or other natural languages, which may function like linguistic universals in constraining the search over possible grammars.…”
Section: Related Workmentioning
confidence: 99%
“…Other linguistic constraints and heuristics such as constraints of root nodes (Noji, Miyao, and Johnson 2016), attachment rules (Naseem et al 2010), acoustic cues (Pate and Goldwater 2013), and punctuation as phrasal boundaries (Seginer 2007a;Ponvert, Baldridge, and Erk 2011) have also been used in induction. More recently, neural PCFG induction systems (Jin et al 2019;Kim et al 2019;Kim, Dyer, and Rush 2019) and unsupervised parsing models (Shen et al 2018(Shen et al , 2019Drozdov et al 2019) have been shown to predict accurate syntactic structures. These more complex neural network models may not contain explicit biases, but may contain implicit confounding factors implemented during development on English or other natural languages, which may function like linguistic universals in constraining the search over possible grammars.…”
Section: Related Workmentioning
confidence: 99%
“…A ∝ exp(H in H out ) (4) The MLP architecture follows Kim et al (2019), with details in the appendix. This factorized parameterization, shown in Figure 1, reduces the total parameters to O(h 2 + h|Z| + h|X |).…”
Section: Scaling Hmmsmentioning
confidence: 99%
“…Probabilistic context-free grammars (PCFGs) are undoubtedly the most thoroughly studied of probabilistic grammars. Due to their ability to capture hierarchical structure in language, and the existence of good learning models, PCFGs have been ubiquitous in computational approaches to language and grammar (see, e.g., Klein and Manning 2003;Levy 2008;Kim et al 2019). But they have also seen many applications in other areas of psychology, for example, as encoding a probabilistic hypothesis space for concepts (Tenenbaum et al, 2011).…”
Section: Probabilistic Context-free Grammarsmentioning
confidence: 99%
“…The driving motivation for early theoretical work on formal grammars came from the psychology of language, where the focus was on finding adequate frameworks for describing and explaining human grammatical competence (Chomsky, 1959(Chomsky, , 1965Chomsky and Schützenberger, 1963). With increased emphasis on detailed processing, parsing, and acquisition accounts, in addition to large-scale grammar induction from corpora in computational linguistics, a considerable amount of applied work has explored probabilistic grammars (see, e.g., Klein and Manning 2003;Levy 2008;Kim et al 2019 for representative examples), the straightforward result of adding probabilistic transitions to classical grammar formalisms. Here again, much of the interest has been to find formalisms that are powerful enough-but not too powerful-to capture relevant linguistic structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation